Assessing the Variability of Tax Elasticities in Lithuania - Poghosyan, Tigran (IMF Working Papers; Working Paper ;, 2011)
This paper quantifies the variability of tax elasticities in Lithuania using two alternative methods: rolling regressions and pooled mean group estimator. The analysis is motivated by the systematic variation of tax revenues observed over the economic cycle in the recent past. Both methods confirm that tax elasticities moved with the cycle, which can be attributed to the procyclical tax compliance tendencies and structural composition effects across tax bases. Comparison of VAT revenue gaps across Baltic countries during the recent recovery suggests that tax revenues rebounded fastest in Estonia, followed by Lithuania and Latvia. Overall, the results of the study emphasize the importance of accounting for cyclical variation in tax elasticities when making short-term tax revenue projections.